La reflexión traductora desde la antigüedad romana hasta el siglo XVIII: una propuesta de interpretación (Minerva. Revista de Filología Clásica, 2019)
This article presents a brief history of the theory of translation from the beginnings of Latin literature up to the 18th century. The author’s argument is that Ciceronian distinction between the activity of the interpres (translating) and that of the orator (paraphrasing) remained virtually unchanged until well-advanced the 18th century. Therefore, such an extensive period of time could be called the “arcaic stage of the theory of translation”